EVALUATION OF GEOMETRIC ERROR OF CUSTOMIZED CNC MILLING MACHINE TOOLS ACCORDING TO ISO 10791-7 - Prayoga, Benidiktus Tulung; Hendaryanto, Ignatius Aris; Winarno, Agustinus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Due to open technology, there exists an abundance of inexpensive information accessible for study. One such piece of information pertains to customization or do-it-yourself (DIY) CNC milling machines. However, customized milling machines often suffer from several limitations, including a lack of component dimension accuracy, inappropriate interaction between components, low rigidity, and control system problems, all of which can impact the cutting performance and accuracy of the workpieces. This study aimed to measure the extent of these impacts on the accuracy of the workpieces. The errors in customized CNC milling machines were identified using a ball-bar system and cutting tests conducted according to ISO standards. The results of this study concluded that improvements must be made to the interaction between machine components to reduce geometric errors to levels acceptable according to standards. This customized CNC milling shows promise for machining workpieces with an accuracy of ± 0.2 mm.